The medicinal value of Amaryllidaceae and Asteraceae species used in male circumcision - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2013)
Thesis (DPhil (Plant Physiology))--University of Pretoria, 2007.